Studying age-related changes in white matter microstructure in healthy aging using noninvasive MRI techniques - Mendez Colmenares, Andrea, author; Thomas, Michael L., advisor; Burzynska, Agnieszka Z., advisor; Rojas, Donald C., committee member (Colorado State University. Libraries, 2020)
Age-related deterioration of the white matter (WM), such as demyelination, is an important mechanism of cognitive decline in healthy aging. Lifestyle factors can influence the course of WM aging. Most evidence have used diffusion tensor imaging (DTI) metrics, but these are not specific to myelin or axons. Therefore, in this study we compared DTI metrics to a proposed proxy of myelin content, the T1-weighted image (T1-WI) to T2-weighted image (T2-WI) ratio with respect to their ability to: detect time-by-intervention interactions, predict processing speed ability, and their correlations with each other and age. We used longitudinal data from 169 cognitively healthy older adults (60-79yrs). MRI imaging (3T Siemens Trio) included 0.9mm3 MPRAGE, 1.7×1.7x3mm3 T2w and DTI (30 diff. dir., bval= 0 and 1000s/mm2, 1.7×1.7x3mm3). T1w/T2w was calculated using internal intensity calibration. We used FSL-FDT to extract DTI metrics, focused on major WM tracts using tract-based spatial statistics in FSL. From the WM skeleton, we calculated mean values for 12 regions-of-interest. Processing speed was assessed using the Virginia Cognitive Aging Battery. Results showed that the T1w/T2w produced greater time-by-intervention interactions than DTI-FA, especially in the posterior (β=0.27, p=0.01) and anterior (β=0.33, p=0.01) limb of the internal capsule. The T1w/T2w (in the whole WM) correlated with processing speed (β=-0.13, p=0.02). T1w/T2w correlated with DTI in regions with high fiber coherence/high myelin content; and with age in regions with high myelin content. Results suggest that the T1w/T2w offers greater ability than DTI to detect short-term longitudinal changes in WM, but they seem to reflect different microstructural properties in the WM. Further research is needed to gain a better understanding of its biological underpinnings and significance.
Keywords: dementia; myelin; white matter; MRI; aging; neurosciences